THE EFFECT OF DHIKR ON ANXIETY AND DEPRESSION LEVEL IN HEMODIALYSIS PATIENTS AT PURWOKERTO ISLAMIC HOSPITAL - Muhamad Anggun; Titik Kusumawinakhyu; Wiharto; Irma Finurina Mustikawati (International Journal of Islamic and Complementary Medicine, 2021)
Hemodialysis is a routinely performed therapy on chronic kidney patients, leading to psychological problems among subjects who undergo hemodialysis, such as anxiety and depression. One of the efforts to overcome anxiety and depression is with the dhikr intervention. Dhikr presents hearts to remember and be obedient to Allah followed by the words and actions in various conditions. Discover dhikr's influence on the level of anxiety and depression in patients on hemodialysis in Purwokerto Islamic Hospital. It was a quantitative study using quasi experiment with a non-quivalent control group design. The number of samples was 12 subjects consisting of 6 subjects in the control group and six subjects in the intervention group with the purposive sampling technique. Instruments were used to measure anxiety and depression are the HADS ( Hospital Anxiety and Depression Scale ) before and after dhikr intervention as much as 12 times. Research is carried out in Hemodialysis Unit of Purwokerto Islamic Hospital. Test statistics on research are used paired t-test and independent t-tests. This study showed a decrease in the mean level of anxiety from 5, 83 to 1.67 in the experimental group ( p = 0.003). The mean level of depression experienced a decline of 9, 67 becomes 4.67 on a group experiment ( p = 0.003). Dhikr reduces the level of anxiety and depression in hemodialysis patients at the Purwokerto Islamic Hospital.